Beneficial effects of public sector performance measurement - Neda Vitezić (Central European Public Administration Review)
Recently, major attention has been devoted to performance measurement in public sector, especially from the aspects of qualitative assessment. For that reason the financial performance measures are limited in overall assessment of an organisation performance. There are also difficulties in quality measurement because of a variety of different services and their intertwinement. New tools, such as balanced system of indicators, customer relation management, benchmarking etc. are subjects of research and implementation. Transition countries follow the trends in developed countries; thus, the obligation to monitor and provide information on public sector performance becomes a part of their legislature. This primarily refers to spending of public revenues, i.e. rationality of performance, while the qualitative aspect or effectiveness is still not measured. The problem lies in the need for a clear vision definition and in goal setting. Realisation of goals and their measurement is related to a well-set strategy and reasonable planning, as well as the selection of adequate indicators. However, the fact remains that setting of measurable goals prompts responsibility of executive power and individuals, as well as transparency in reporting. The benefits of performance measurement become evident also in the practice of emerging countries, and they are related to behaviour changing, transparency, accountability, organisation and leadership improvements, and willingness to learn and to innovate processes.